A Review on Homogeneous Charge Compression Ignition Engine Performance using Biodiesel–Diesel Blend as a Fuel - M. M., Hasan; M. M., Rahman; K., Kadirgama (Universiti Malaysia Pahang, 2015)
Homogeneous charge compression ignition (HCCI) engines employ a relatively new mode of combustion technology, in which auto-ignition occurs when the lean mixture of air and fuel reaches its chemical activation energy. It is a combustion concept that offers simultaneous reductions in both NOx and soot emissions from internal combustion engines. A wide range of fuels can be used in this engine. Of these, diesel and biodiesel–diesel blends are most common. The objective of this study is to illustrate the fuel properties, engine performance and emission characteristics of the mentioned fuels at different conditions performed worldwide in HCCI engines, as well as to compare HCCI engines with conventional compression ignition (CI) engines in respect of engine combustion, performance and emission characteristics. This may also introduce a potential guideline to improve engine performance and emission characteristics using diesel and its blends. From the review, it can be said that using diesel and its blends in HCCI engines with biodiesel can improve the overall engine performance and emission characteristics in comparison with CI engines.